2007
DOI: 10.1185/030079907x178685
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide versus insulin glargine in patients with type 2 diabetes in the UK: a model of long-term clinical and cost outcomes

Abstract: Based on the findings of a recent clinical trial, long-term projections indicated that exenatide is likely to be associated with improvement in life expectancy and quality-adjusted life expectancy compared to insulin glargine. The results from this modelling analysis suggest that that exenatide is likely to represent good value for money by generally accepted standards in the UK setting in individuals with type 2 diabetes inadequately controlled on oral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 45 publications
3
32
2
Order By: Relevance
“…One study set in the United Kingdom evaluated the life-expectancy associated with exenatide versus insulin glargine, as add-on therapies in T2D patients inadequately controlled on combination OADs after 35 years of treatment. 84 Using a computer simulation model of diabetes (CORE model) and data from a published head-to-head 26-week trial of exenatide versus insulin glargine in 549 patients, it was demonstrated that exenatide was associated with both improvements in life expectancy and qualityadjusted life-expectancy. When compared with insulin glargine, life expectancy improved by 0.057 years with exenatide, while quality-adjusted life years improved by 0.442.…”
Section: Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…One study set in the United Kingdom evaluated the life-expectancy associated with exenatide versus insulin glargine, as add-on therapies in T2D patients inadequately controlled on combination OADs after 35 years of treatment. 84 Using a computer simulation model of diabetes (CORE model) and data from a published head-to-head 26-week trial of exenatide versus insulin glargine in 549 patients, it was demonstrated that exenatide was associated with both improvements in life expectancy and qualityadjusted life-expectancy. When compared with insulin glargine, life expectancy improved by 0.057 years with exenatide, while quality-adjusted life years improved by 0.442.…”
Section: Deathmentioning
confidence: 99%
“…The authors attributed the difference between life expectancy and quality-adjusted life expectancy to the impact of exenatide's body-weight lowering effect on improving lifestyle. 84 The long-term cardiovascular morbidity and mortality effects of treatment with liraglutide were also simulated using the CORE diabetes cohort model, with data extracted from LEAD-1. 85 Simulating a hypothetical cohort of 5000 patients per treatment (liraglutide 1.2, 1.8 mg, rosiglitazone 4 mg, all added to glimepiride), this model estimated that the survival rates would be 15% and 16% higher for liraglutide 1.2, 1.8 mg respectively than rosiglitazone after 30 years of treatment.…”
Section: Deathmentioning
confidence: 99%
“…77 The most common comparison, reported in four studies, was between exenatide and glargine. 74,[77][78][79] Three of the studies, which were conducted in Switzerland, Germany, and the UK, concluded that exenatide was cost effective relative to glargine with cost per QALY ranging from €13,764 to €29,401 (£34,631 at an exchange rate of 1.178 Euro to British Pound). 74,77,78 Cost effectiveness was sensitive to weight change and occurrence of nausea.…”
Section: Economic Modelsmentioning
confidence: 99%
“…74,[77][78][79] Three of the studies, which were conducted in Switzerland, Germany, and the UK, concluded that exenatide was cost effective relative to glargine with cost per QALY ranging from €13,764 to €29,401 (£34,631 at an exchange rate of 1.178 Euro to British Pound). 74,77,78 Cost effectiveness was sensitive to weight change and occurrence of nausea. When these factors were ignored, costs per QALY for between the approaches, including assumptions about the development of complications, which were all based on UKPDS data, the models generated different estimates for QALY gained.…”
Section: Economic Modelsmentioning
confidence: 99%
See 1 more Smart Citation